Pengaruh Kualitas Produk Terhadap Kepuasan Konsumen pada Usaha Es Cendolita Bu Wiwin - Priska Emannuela Kusuma; Innez Indah Putri; Dwi Astuti (CV. ITTC INDONESIA, 2025)
Customer satisfaction is a fundamental element in business success, especially in the small and medium enterprise (SME) sector which has limited resources but faces increasingly fierce competition. This satisfaction is closely related to the business's ability to meet or exceed customer expectations, which in turn can drive loyalty, positive reviews, and long-term growth. In the context of Bu Wiwin's Es Cendolita Business, efforts to understand the effect of product quality on customer satisfaction are important to ensure the sustainability and competitiveness of the business. This study aims to analyze how aspects of product quality, such as taste, cleanliness, and aesthetic presentation, affect the level of customer satisfaction. Using a qualitative approach, data were collected through in-depth interviews with consumers, direct observation of the production and presentation processes, and documentation of customer reviews and sales data. Interviews provide insight into consumer perceptions of product quality and their overall experience. The results of the study indicate that product quality has a significant effect on consumer satisfaction at Bu Wiwin's Es Cendolita Business. Aspects of product quality, including taste, cleanliness, and attractive presentation, have been shown to be the main factors driving positive customer experiencesCustomer satisfaction is a fundamental element in business success, especially in the small and medium enterprise (SME) sector which has limited resources but faces increasingly fierce competition. This satisfaction is closely related to the business's ability to meet or exceed customer expectations, which in turn can drive loyalty, positive reviews, and long-term growth. In the context of Bu Wiwin's Es Cendolita Business, efforts to understand the effect of product quality on customer satisfaction are important to ensure the sustainability and competitiveness of the business. This study aims to analyze how aspects of product quality, such as taste, cleanliness, and aesthetic presentation, affect the level of customer satisfaction. Using a qualitative approach, data were collected through in-depth interviews with consumers, direct observation of the production and presentation processes, and documentation of customer reviews and sales data. Interviews provide insight into consumer perceptions of product quality and their overall experience. The results of the study indicate that product quality has a significant effect on consumer satisfaction at Bu Wiwin's Es Cendolita Business. Aspects of product quality, including taste, cleanliness, and attractive presentation, have been shown to be the main factors driving positive customer experiences